CORRELATION OF CT AND ULTRASOUND MORPHOMETRY OF THE ABDOMINAL WALL WITH PATHOMORPHOLOGICAL CHANGES IN POSTOPERATIVE VENTRAL HERNIAS (Global Conference on Medical and Health Sciences, 2026)
The degree of destructive changes in the musculoaponeurotic tissues of the abdominal wall is one of the most important factors influencing the immediate results of hernia repair and recurrence rates. Clinical examination and conventional radiography cannot objectively assess the anatomical and functional state of the abdominal wall, which makes it necessary to validate imaging morphometry against tissue pathomorphology.